Effect of Carbon Nanotube Content and Mechanical Milling Conditions on the Manufacture of AA7075/MWCNT Composites - Iria Feijoo; Gloria Pena; María Julia Cristóbal; Marta Cabeza; Pilar Rey (Metals, 2022)
Aluminium matrix composites (AlMCs) of AA7075 aluminium alloy reinforced with 0.5 and 1 wt.% multiwall carbon nanotubes (MWCNTs) were fabricated with powder metallurgy techniques using three different mechanical milling strategies, varying the milling energy and the stage in which the reinforcements were added to the pre-alloyed matrix powders. In this paper, we focus on the influence of these parameters on the dispersion of MWCNTs. Characterization of the obtained composite powders by X-ray diffraction and scanning electron microscopy showed that the evolution of the particle size and morphology of the composite powders is influenced by milling conditions and MWCNT content; however, under the conditions tested in this study, there were no significant differences in crystallite size and lattice strain. The best distribution of the reinforcements was obtained after milling 7075 powders and MWCNTs in a high-energy cycle (HEBM), varying the rotation speed between 1200 and 1300 rpm. Raman spectroscopy was used to assess the damage induced by the milling process in the nanotubes, and no reaction products were detected under any of the tested conditions. Nanoindentation tests were performed to measure the elastic modulus and hardness of the composite powders, revealing that the best mechanical behaviour was achieved by the 7075-0.5 wt.% MWCNT composites obtained by the HEBM route.